Pengaruh Startifikasi Dalam Kenyataan Hukum - Basyirah Mustarin (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2021)
AbstractSo far, there have been many rather surprising events related to law enforcement (sanctions) imposed on classes of society who occupy positions with people who do not occupy positions at all, in fact there is an opinion circulating in the community that